2012
DOI: 10.2174/092986712801215847
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Anticoagulants

Abstract: Warfarin, heparin and their derivatives have been the traditional anticoagulants used for prophylaxis and treatment of venous thromboembolism. While the modern clinician is familiar with the efficacy and pharmacokinetics of these agents, their adverse effects have provided the impetus for the development of newer anticoagulants with improved safety, ease of administration, more predictable pharmacodynamics and comparable efficacy. Research into haemostasis and the coagulation cascade has made the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 121 publications
1
42
0
1
Order By: Relevance
“…For instance, hirudin (a thrombin inhibitor from leeches) and its congener bivalrudin have been useful in the treatment of blood coagulation disorders (Kennedy et al, 2012). Ticks are parasites that have evolved multiple ways to evade or manipulate host immune and hemostatic systems (Chmelar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, hirudin (a thrombin inhibitor from leeches) and its congener bivalrudin have been useful in the treatment of blood coagulation disorders (Kennedy et al, 2012). Ticks are parasites that have evolved multiple ways to evade or manipulate host immune and hemostatic systems (Chmelar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Such control of the metal environment through modification of the structure external to the coordination sphere often leads to a change in the spin and/or oxidation states of the metal center, [1,2] which is of great importance not only for understanding the functionalities of biological systems but also for constructing coordination systems that show unique molecular structures and properties coupled with the electronic states of their metal centers. The anomalous stability of the +II oxidation state of each octahedral cobalt center in [2], despite the coordination of two aliphatic amine and two aliphatic thiolato groups that commonly provide a strong ligand field, is notable. [3][4][5] penicillamininate], which are stereoselectively prepared from the reaction of a tripod-type trigold(I) metalloligand [Au 3 (tdme)(D-pen) 3 ] 3-( [1] 3-) with Co 2+ and Co 3+ , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Compound [1] 3was found to bind to Co 2+ in a bridging mode to give a Co II 3 Au I 6 nonanuclear structure in [Co II 3 {Au 3 (tdme)(d-pen-N,O,S) 3 } 2 ] ( [2]) with a fascinating ball-like shape, whereas [1] 3coordinates to Co 3+ in a chelating mode to produce a relatively simple Co III Au I 3 tetranuclear structure in [Co III {Au 3 -(tdme)(d-pen-N,S) 3 }] ([3]) (Scheme 1). This system was created from the trigold(I) complex [Au 3 (tdme)(d-pen) 3 ] 3-([1] 3-) bearing commercially available 1,1,1-tris[(diphenylphosphino)methyl]ethane (tdme) and d-penicillaminate (d-pen) ligands, and it can function as a chelating or bridging metalloligand by using the three d-pen moieties.…”
Section: Introductionmentioning
confidence: 99%
“…[3,10,16] The design of metal sites in de novo designed metallopeptides will be presented in the next section and has been reviewed in detail elsewhere. [3,10,16,77,78] Here it is worth noting that the substitution of one hydrophobic residue in the peptide sequence by a coordinating residue (e.g., Cys, His, Glu) allows the preparation of homomeric three-stranded coiled coils that possess an M(X) n site in the interior (with C nv symmetry) ( Figure 4). This site can be positioned close to the center of the coiled coil or close to the N or C termini of the helices depending on the position of the mutated Leu in the sequence.…”
Section: De Novo Designed α-Helical Scaffoldsmentioning
confidence: 99%
“…[9,18,44] Hard versus soft donor groups have been employed, for instance, to design metal-binding sites with different hard/soft character in TRI or IZ three-stranded coiled coils. [3,10,16,44,59,78] The modulation of the reactivity of a metal site through the design of the second coordination sphere is one of the principal paradigms in protein redesign, [14,17,103] but several examples have shown that it is also applicable to minimum helical scaffolds. [25,26,28,29,76,102] Interestingly, metals such as mercury are not known to have a structural role in molecular biology.…”
Section: Design Of Structural and Functional Metal Sitesmentioning
confidence: 99%